Preface: From Avukah to Worker Self Management (AmeriQuests, 2016)
This article explains some of the forces that shaped some of Lawrence B. Cohen's ideas, most notably his involvement in Avukah and his association with Seymour Melman and Zellig Harris, key members and then directors of that organization. Cohen's ideas are then adopted into a general framework that Zellig Harris employed in his thinking about the transformation of capitalist society, outlined in a book by the same name.
Keywords: avukah; barsky; melman; chomsky; Zellig Harris